The impact of Basel III on money creation: A synthetic analysis - Wanting Xiong; Yougui Wang (Kiel Institute for the World Economy (IfW), 2017)
Recent evidences provoke broad rethinking of the role of banks in money creation. The authors argue that apart from the reserve requirement, prudential regulations also play important roles in constraining the money supply. Specifically, they study three Basel III regulations and theoretically analyze their standalone and collective impacts. The authors find that 1) the money multiplier under Basel III is not constant but a decreasing function of the monetary base; 2) the determinants of the bank's money creation capacity are regulation-specific; 3) the effective binding regulation and the corresponding money multiplier vary across different economic states and bank balance sheet conditions.
Keywords: E51; G28; G18; E60; 330; money creation; Basel III; liquidity coverage ratio; capital adequacy ratio; leverage ratio; money multiplier